Study on the physicochemical and flavor characteristics of air frying and deep frying shrimp (crayfish) meat - Zhou, Mingzhu; Shi, Gangpeng; Deng, Yi; Wang, Chao; Qiao, Yu; Xiong, Guangquan; Wang, Lan; Wu, Wenjin; Shi, Liu; Ding, Anzi (Frontiers in Nutrition, 2022)
This study aimed to compare the changes in the quality characteristics of air-fried (AF) shrimp meat and deep-fried (DF) shrimp meat at different frying temperatures (160, 170, 180, 190°C). Results showed that compared with DF, the moisture and fat content of air-fried shrimp meat (AFSM) was lower, while the protein content was higher. At the same frying temperature, the fat content of the AFSM was 4.26–6.58 g/100 g lower than that of the deep-fried shrimp meat (DFSM). The smell of the AFSM and DFSM was significantly different from that of the control group. The results of the electronic tongue showed that each of the two frying methods had its flavor profile. Gas chromatography-ion mobility spectrometry (GC-IMS) identified 48 compounds, and the content of volatile compounds detected in AFSM was lower than that in DFSM. Among them, the highest level of volatile compound content was found in the DF-190. E-2-pentenal, 2-heptenal (E), and methyl 2-methyl butanoate were identified only in DFSM. In addition, a total of 16 free amino acids (FAAs) were detected in shrimp meat. As judged by sensory evaluation, the AFSM at 170°C was the most popular among consumers.